2007
DOI: 10.1111/j.2007.0906-7590.05083.x
|View full text |Cite
|
Sign up to set email alerts
|

Gall‐forming and free‐feeding herbivory along vertical gradients in a lowland tropical rainforest: the importance of leaf sclerophylly

Abstract: In contrast to most insect guilds, gall-forming insects are thought to reach highest diversity on sclerophyllous vegetation, such as Neotropical savannas and Mediterranean vegetation types. The water and nutrient stress endured by meristems of canopy trees in tall wet tropical rainforests may cause leaf sclerophylly. Hence, the upper canopies of such ecosystems may represent a suitable habitat for gall-forming insects. At the San Lorenzo Protected Area, Panama, we estimated free-feeding herbivory and gall dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 78 publications
(18 citation statements)
references
References 36 publications
3
13
0
2
Order By: Relevance
“…We expect both groups to be more parasitized lower in the canopy, but we expect semiconcealed hosts to be more abundant higher in the canopy, in accordance with the hypothesis that the harsh upper canopy environment favors concealed or semiconcealed feeders (Ribeiro & Basset, 2007). Moreover, in tropical forests, there are differences in parasitoid community composition between exposed and semiconcealed feeders (Hrcek, Miller, Whitfield, Shima, & Novotny, 2013), and here, we expect a similar pattern.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…We expect both groups to be more parasitized lower in the canopy, but we expect semiconcealed hosts to be more abundant higher in the canopy, in accordance with the hypothesis that the harsh upper canopy environment favors concealed or semiconcealed feeders (Ribeiro & Basset, 2007). Moreover, in tropical forests, there are differences in parasitoid community composition between exposed and semiconcealed feeders (Hrcek, Miller, Whitfield, Shima, & Novotny, 2013), and here, we expect a similar pattern.…”
Section: Introductionsupporting
confidence: 83%
“…Therefore, the higher diversity recorded in the first level might be due to the involvement of understory species, supporting our original hypothesis. The higher diversity of the third level might be explained by the presence of species‐rich semiconcealed feeders, which were considerably less numerous in the first level, supporting the original hypothesis of the competitive advantage of the concealed feeders in the harsh upper canopy environment (Chaij et al., 2016; Paniagua et al., 2009; Ribeiro & Basset, 2007). However, in our study, due to the absence of the upper canopy per se, differences in the ecological conditions (e.g., solar radiation, temperature, wind speed; Basset, Horlyck, et al., 2003; Parker, 1995) between the second and third levels were blurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental stress hypothesis (ESH) predicts that gallinducing insect diversity should be greater in more stressful/xeric habitats (Fernandes & Price, 1988). The mechanisms underlying greater species richness in xeric habitats involve evolutionary and ecological processes (Fernandes & Price, 1988;Price, Fernandes, & Waring, 1987;Ribeiro & Basset, 2007). Among ecological mechanisms, the actions of parasites and predators (third trophic level) are thought to be less effective at regulating gall-inducing insect diversity in xeric habitats, thus leading to greater diversity of gallers in such habitats (Castellanos, Cuevas-Reyes, Rios-Casanova, Oyama, & Quesada, 2006).…”
mentioning
confidence: 99%
“…Studies have also shown that plants growing on water-and nutrient-deprived soils are more sclerophyllous (Poorter, Niinemets, Poorter, Wright, & Villar, 2009) and accumulate higher levels of chemical compounds . Thus, internalfeeding gall-inducing insects attacking such plants would experience greater protection from their natural enemies (Hardy & Cook, 2010;Ribeiro & Basset, 2007). These hypotheses have been supported by several studies conducted in tropical (Fernandes, Gonçalves-Alvim, & Carneiro, 2005;Jesus, Silva, & Fernandes, 2012;Julião, Almada, & Fernandes, 2014;Lara, Fernandes, & Gonçalves-Alvim, 2002) and temperate (Fernandes, Duarte, & Lüttge, 2003;Fernandes & Price, 1988 habitats.…”
mentioning
confidence: 99%